Academic House Style and Acknowledgement Writing: the Case of Two Ghanaian Universities - Cecilia Agyeiwah Agyemang Owusu Debrah; Alberta Dansoah Nyarko Ansah (Universitas Islam Negeri Walisongo Semarang, 2022)
This descriptive study sought to examine the structural features of Thesis Acknowledgements (TA) from two disciplines in two Ghanaian Universities. Forty TAs were sampled from the fields of Chemistry and English. Hyland’s (2004) generic move structure was modified in analyzing the sampled TAs. The data was also examined on the basis of the two institutions’ academic style guides for conformity. The findings indicate that the structural features of TAs from the two fields differ. It also revealed that out of the seven steps identified in the obligatory Elaborative Move, DoC writers generally use three steps, and DoE writers mostly use four steps. It is further revealed that while writers from the DoC mostly acknowledged contributors for their technical support, writers from DoE acknowledged their helpers for providing materials for the research. It was revealed that the data followed the institutional style guide. The paper argues that though the contextual difference in the TAs from both fields is minimal, subtle variances and parallels still exist between the two fields. Therefore, it is suggested that these variations in linguistic forms that account for the discursive styles of the TAs should be further examined. Finally, additional analysis by corpus analytic tools applied to large data from the research context could complement this study.